Europa: społeczność coraz bardziej złożona i zróżnicowana. Młodzież między immanencją i transcendencją - Ebertz, Michael N. (Studia Pastoralne, 2026)
International comparison shows, that religiousness (Christianness and churchliness) in a process of social integration and individual optimalisation loses its normative character, traditional stability and the institutional control. It becomes an opportunity of self-education that is no longer understood as external instructions. Such a process, although not simultaneous one, takes place in various countries across Europe. More and more young people decide for themselves which spheres of their lives will operate within a religious framework, and which not, which religious interpretation will they accept from the Tradition of the Church, which rituals will they need. It is closely related to the issue of a statistic correlation. The Church transforms herself more and more and makes a certain religious offer, especially to youth, that recognises man and transforms religious subjects into conscious religious clients. Chances of transferring the Good News to the next generations depend on the way the Church deals with certain pressures and expectancies concerning her becoming a “service organisation”.